2017
DOI: 10.1002/cphg.26
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem (hiPS) Cells from Urine Samples: A Non‐Integrative and Feeder‐Free Reprogramming Strategy

Abstract: Human induced pluripotent stem (hiPS) cell technology has already revolutionized some aspects of fundamental and applied research such as study of disease mechanisms and pharmacology screening. The first clinical trial using hiPS cell-derived cells began in Japan, only 10 years after the publication of the proof-of concept article. In this exciting context, strategies to generate hiPS cells have evolved quickly, tending towards non-invasive protocols to sample somatic cells combined with "safer" reprogramming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 29 publications
0
21
0
3
Order By: Relevance
“…Moreover, the u-d hiPSC did not correlate more with the parental urine-derived cells than hESCs or the f71 hiPSCs. Finally, urine-derived cells specific genes MCAM, PAX8 and NT5E 21 , 27 did not show persistence in u-d hiPSCs compared to hESCs or f71 hiPSCs (Fig. 2c ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, the u-d hiPSC did not correlate more with the parental urine-derived cells than hESCs or the f71 hiPSCs. Finally, urine-derived cells specific genes MCAM, PAX8 and NT5E 21 , 27 did not show persistence in u-d hiPSCs compared to hESCs or f71 hiPSCs (Fig. 2c ).…”
Section: Resultsmentioning
confidence: 92%
“…Finally, we repeated the reprogramming of patient 149 cells to establish hiPSC directly on Matrigel, a commonly used coating matrix. We were able to generate feeder-free hiPSC lines, as recently published for episomal reprogramming of urine-derived cells 21 (Fig. 1d ).…”
Section: Resultsmentioning
confidence: 93%
“…No free DNA was detected in iPSCs after 8 passages, which further indicated that iPSCs were not well integrated into the experiment [40]. Researchers have used free vectors to transfect transcription factors such as Oct4, Sox2, Lin28, l-myc, and Klf4 into urine cells, while added free vectors which mediated the EBNA1 gene expression, as well as a P53 knockout to improve reprogramming efficiency [24]. ese methods eventually generated successful iPSCs.…”
Section: Episomal Vectorsmentioning
confidence: 99%
“…Furthermore, USCs do not express hematopoietic stem cell markers such as CD25, CD31, CD34, and CD45. Simultaneously, researchers have reported that USCs in the urine are the main source of the iPSCs [24].…”
Section: Introduction Of Urine-derived Cellsmentioning
confidence: 99%
See 1 more Smart Citation